Modern concept about the vaginal biocenosis of adolescent girls and its changes - M. Yu. Akhmetova; V. V. Florensov; O. Ya. Leshchenko; O. E. Baryaeva; L. I. Kolesnikova (Acta Biomedica Scientifica, 2025)
The main representative of the vaginal biocenosis of adolescent girls after menarche and during the reproductive period of life is obligate-anaerobic lactobacilli. Qualitative and quantitative changes in the composition of the vaginal biocenosis occur under the influence of various exogenous and endogenous factors and can contribute to the development of the vulvar and vaginal inflammatory diseases.The  aim of  the review. To  analyze modern literary data on  the  peculiarities of the vaginal biocenosis of adolescent girls, its formation in the age aspect, changes under the influence of adverse factors and in the presence of comorbid diseases. Two hundred fifty foreign and Russian literature sources indexed in RSCI, PubMed, Scopus, SSCI were analyzed, mainly from 2014 to 2024. Sixty-nine sources were used for the article, 23 of them published in the last 5 years.Results. Most studies emphasize the fact that it is necessary to carefully examine adolescent girls with identified risk factors for violations of vaginal biocenosis, including comorbid diseases.